Impresje „archiwisty”… - Berkan-Jabłońska, Maria (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The article addresses some aspects of the work in the archives in Vilnius. The author emphasizes that the Vilnius archives contain a lot of valuable literary documents and materials relating to the Polish literature, especially of the period 1830–1870, which is less known. Meanwhile, it is difficult to conduct a query. First, there are only a few catalogs of Vilnius collections that do not contain all the units included in the archival fonds.Second difficulty is the language, because the descriptions in the catalogs are usually in Lithuanian or Russian, even though they concern Polish-works. Thirdly, only a small percentage of the Polish part of the collections is digitized, so ephemeral sets quickly deteriorate. If we want to preservethe legacy of the borderland, we must find a way to support the queries in Vilnius, based on scientific and institutional Polish-Lithuanian cooperation.